1997
DOI: 10.1016/s0014-5793(96)01476-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of aminopeptidase N and endopeptidase 24.15 inhibitors potentiate behavioral effects mediated by nociceptin/orphanin FQ in mice

Abstract: The behavioral effects induced by central administration in mice of the endogenous ORLj (opioid receptor-like]) ligand, nociceptin/orphanin FQ, were investigated in the absence or presence of inhibitors of aminopeptidase N (bestatin) and endopeptidase 24.15 (Z-(L!D) PheT(P0 2 CH 2 )(L,D)Ala-Arg-Phe) recently shown to be involved in the metabolism of the heptadecapeptide in vitro. A severe reduction in motor activity induced by nociceptin/orphanin FQ was measured in two tests (spontaneous motor activity and ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 24 publications
(33 reference statements)
4
31
1
Order By: Relevance
“…2) In contrast, mice injected with 0.1 and 0.3 nmol showed a decrease in locomotor activity and muscular tone (especially in the hindpaws), ataxia, and loss of the righting reflex; however, a normal tail-pinch reflex was maintained. These behavioral effects of [Arg 14 ,Lys 15 ]NC were very similar to those evoked by high doses (i.e., 10 nmol) of NC, as reported by several investigators (Reinscheid et al, 1995;Devine et al, 1996;Noble and Roques, 1997;Calo' et al, 1998b [Arg 14 ,Lys 15 ]Nociceptin, a Potent OP 4 Receptor Agonist pared with saline. This effect was statistically significant for 0.1 and 0.3 nmol (p Ͻ 0.05 according to ANOVA followed by the Dunnett test).…”
Section: Insupporting
confidence: 86%
“…2) In contrast, mice injected with 0.1 and 0.3 nmol showed a decrease in locomotor activity and muscular tone (especially in the hindpaws), ataxia, and loss of the righting reflex; however, a normal tail-pinch reflex was maintained. These behavioral effects of [Arg 14 ,Lys 15 ]NC were very similar to those evoked by high doses (i.e., 10 nmol) of NC, as reported by several investigators (Reinscheid et al, 1995;Devine et al, 1996;Noble and Roques, 1997;Calo' et al, 1998b [Arg 14 ,Lys 15 ]Nociceptin, a Potent OP 4 Receptor Agonist pared with saline. This effect was statistically significant for 0.1 and 0.3 nmol (p Ͻ 0.05 according to ANOVA followed by the Dunnett test).…”
Section: Insupporting
confidence: 86%
“…NEP 24.11 appears to be less important in the brain, where aminopeptidase N and endopeptidase 24.15 have been indicated as the main enzymes responsible for NC degradation. 14,15 We found that the fragment NC(1-9)NH 2 , which does not alter MBP, tends to induce tachycardia, an effect opposite to that evoked by NC. Further studies are necessary to determine whether this action is due to interaction of NC(1-9)NH 2 with unrelated receptors or to other unforeseen properties of the fragment.…”
Section: Discussionmentioning
confidence: 71%
“…Its location on the cell surface mandates that its functional activity is dictated by substrates that are available in the immediate intercellular space. CD13/APN has been implicated in the catabolism of neuroactive peptides, [32][33][34] amino acid scavenging and degradation of regulatory peptides, 35,36 cell adhesion alterations, 37 tumor invasion and metastasis, 38,39 as well as antigen processing and presentation. 40,41 Because the switch from the quiescent to angiogenic endothelial phenotype involves an alteration in the relative levels of angiogenic inhibitors and activators, 1 it is intriguing to postulate a role for CD13/APN in the processing of small regulatory molecules required to initiate, maintain, or suppress the angiogenic program in tumor vessel endothelium.…”
Section: Discussionmentioning
confidence: 99%